ENGINEERING AIR CONDITIONING SYSTEMS ON MOVIE THEATRE TO ANTICIPATE COVID-19 AIRBORNE TRANSMISSION - Ajiprayoga Putera, Christopher
At the beginning of 2020, the world was hit by a pandemic that attacked the human respiratory system. WHO has named this disease as COVID-19. This disease is caused by the SARS-CoV-2 virus. This disease can be transmitted through airborne droplets that enter the human respiratory system. Places that use air conditioning systems have a high risk of causing the spread of the virus through the air. Movie theatre is one of the places where there is a high risk of the spread of COVID-19 because of poor ventilation. Therefore, it is necessary to conduct research to minimize the spread of COVID-19 through the air in movie theatre. In this study, an analysis of the current air conditioning system was carried out to see how the potency of the spread of the virus in the movie theatre. Because the existing system is not sufficient to anticipate the spread of the virus, designing a new system is needed. The system design includes ventilation, air flow direction, air recirculation, and filtration. At the end of system design, the selection of the system that is most suitable and most likely to be implemented is carried out. The results of this study indicate that it is necessary to change the ventilation system, especially to meet the ventilation rate of 6 air changes per hour according to SAGE Enviroment and Modelling Group. In addition, it is necessary to change the position of the air outlet to change the direction of air flow to minimize the occurrence of cross-contact infection through the air. The filter used by the system at least is MERV 14.